O dever fundamental de pagar tributos : a atualização da planta genérica de valores do IPTU como imperativo constitucional - Santos, Ramon Rocha (2016)
This paper aims to discuss, in the academic field, a subject forgotten in the Brazilian constitutional debate, namely, the fundamental duties. With support in the European doctrine, especially the Portuguese headed by Professor José Casalta Nabais, seeks to demonstrate the evolution and importance of the constitutional debate about the fundamental duties in the current legal scenario. In an inter relational perspective, the fundamental duties are understood not as restrictions on fundamental rights, but as an autonomous legal category, relating them to a greater or lesser degree, with fundamental rights. In this context, it addressed the fundamental duty to pay taxes, highlighting the importance of tax in the democratic rule of law, building up a new vision of legal tax relationship. The tribute is no longer seen as a rule of social rejection, seeing as a fundamental duty inherent to citizenship and resulting solidarity, serving as an appropriate and necessary instrument for the much desired social change. They are also investigated the ethical and moral issues related to taxation, identifying the acts committed by both the state and taxpayers. Within this perspective is an analysis of the need to update the generic plant property tax values as embodiment of the contributory capacity principle, demonstrating the close relationship of that principle with the principle of social solidarity in order to demonstrate that such update reveals itself as an imperative constitutional.